2014
DOI: 10.1088/1054-660x/24/10/105107
|View full text |Cite
|
Sign up to set email alerts
|

Self-pulsing in a large mode area, end-pumped, double-clad ytterbium-doped fiber laser

Abstract: The characteristics of self-pulsing in a large mode area, end-pumped, double-clad Yb-doped fiber laser are presented. The laser operates in a self-pulsing regime, either by using one or two perpendicularly cleaved ends as the feedback mirrors, while it transforms in a broadband amplified spontaneous emission source when both ends are angle cleaved. In the pulsed regime, up to 2 µs full width at half maximum pulse widths and repetition rates of the order of hundreds of kHz are generated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…It is desirable to have high power fiber laser systems with diffraction limited beam quality, which are attractive sources for many applications, such as the coherent lidar system, nonlinear frequency conversion, and coherent beam combining [1][2][3][4][5][6]. Generally, large mode area (LMA) fibers are employed to mitigate nonlinear effects and enable higher power scaling [7][8][9], which inevitably results in the fiber supporting the propagation of a few modes and the onset of new phenomenon-thermal-induced mode instabilities (MI) [10,11]. The onset of MI degrades the beam quality and currently limits the further power scaling of ytterbium-doped fiber laser systems with diffraction-limited beam quality.…”
Section: Introductionmentioning
confidence: 99%
“…It is desirable to have high power fiber laser systems with diffraction limited beam quality, which are attractive sources for many applications, such as the coherent lidar system, nonlinear frequency conversion, and coherent beam combining [1][2][3][4][5][6]. Generally, large mode area (LMA) fibers are employed to mitigate nonlinear effects and enable higher power scaling [7][8][9], which inevitably results in the fiber supporting the propagation of a few modes and the onset of new phenomenon-thermal-induced mode instabilities (MI) [10,11]. The onset of MI degrades the beam quality and currently limits the further power scaling of ytterbium-doped fiber laser systems with diffraction-limited beam quality.…”
Section: Introductionmentioning
confidence: 99%
“…The traces shown were measured at output 1 of the YDFL. Traces (1) to (4) in figure 4(b) were accomplished by the OSA in 1 min, except for trace (5), accomplished in 15 s; the OSA's resolution and sensitivity were always fixed to 1 nm and '3', respectively. The repetition rate of the sweeping cycles, obtained from the OSA's traces, vs output power is demonstrated in figure 4(c); in turn, the spectral sweeping rate at SLLS grows accordingly-from ∼0.3 nm s −1 (at the laser threshold) to ∼1.0 nm s −1 (when the regime became highly unstable, refer to trace (5), i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This concerns the case of extremely low feedback (Fresnel reflection of less than ∼10 −5 ) at the strongly wedged ends of the YDFs used, allowing the creation of powerful incoherent sources of amplified spontaneous emission (ASE) at ∼1…1.1 µm (see, e.g. [3][4][5]), as in cases of 'moderate' feedback: namely, when the YDF is perpendicularly cleaved from both sides (∼3.5% Fresnel reflection), or when it is placed in a cavity with weakly reflecting couplers (usually fiber Bragg gratings (FBGs)), both resulting in coherent or quasi-coherent light generation at ∼1…1.1 µm in peculiar, somewhat uncommon, operational regimes . In particular, in CW-pumped YDFLs with a low-Q-factor cavity, self-induced laser line sweeping (SLLS) at low (up to ∼1.2 thresholds) pump powers was first observed in 2011 [6,7] and subsequently explored in many other FLs [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That same year, it was reported that although self-sustained pulsations die out quickly in the absence of self-phase modulation (SPM), SPM restores these oscillations when the laser power exceeds a certain value [11]. After four years, the self-pulsing was shown to be produced by the saturable absorption present in not efficiently pumped active fiber sections [12].…”
Section: Introductionmentioning
confidence: 98%